A thermal management system for rectangular LiFePO4 battery module using novel double copper mesh-enhanced phase change material plates. (15th December 2017) - Situ, Wenfu; Zhang, Guoqing; Li, Xinxi; Yang, Xiaoqing; Wei, Chao; Rao, Mumin; Wang, Ziyuan; Wang, Cong; Wu, Weixiong
Abstract: A coupled battery thermal management (BTM) system based on novel quaternary phase change material plate (PCMP) is developed to balance the temperature in rectangular LiFePO4 battery modules. Paraffin (PA), expanded graphite (EG), low-density polyethylene, and copper mesh were combined into a quaternary PCMP to strengthen the heat transfer. The thermal conductivity of the PCMP with double copper mesh (DCM-PCMP) was increased by 36.0% compared with that of PCMP composed of EG and PA. Accordingly, the DCM-PCMP reduced the maximum temperature and maximum temperature difference within the battery module to less than 52.8 and 3 °C, respectively, both the lowest among the four methods. The coupled system based on DCM-PCMP and forced air convection showed excellent thermal performance, which contributed to a stable temperature during the cycling process. Thermal simulations showed that the double outstretched copper mesh through the DCM-PCMP disturbed the air flow tempestuously, giving rise to a decrease in thermal resistance. Thus, the temperature distribution inside the battery and temperature uniformity within the battery module were both better optimized. The analysis of the power consumption of the DCM-PCMP method revealed that the optimal heat dissipation performance for the battery module is achieved at an air velocity of 6 m/s. Highlights: The maximum thermal conductivity of the DCM-PCMP can be obviously improved. The coupled system based on DCM-PCMP and air-cooling significantly enhanced the thermal management effect. The outstretched copper mesh can effectively reduce the internal temperature of the battery. The DCM-PCMP can effectively reduce the power consumption of battery module for secondary cooling.